Pengaruh Gaya Hidup, Brand Image, dan E-Wom terhadap Minat Beli Mahasiswa UNISBA pada Produk Skincare Skintific - Ghina Nabilah; Bambang Septiawan (Jurnal Manajemen Bisnis Digital Terkini, 2024)
The use of technology also plays an important role in selling companies and consumers to dig up information and provide positive or negative opinions about the desired product, which will affect consumer purchasing interest before buying the product. This study aims to analyze the influence of lifestyle, brand image, and e-wom on Unisba students' purchasing interest in Skintific skincare products. The population of this study was 150 management students. The data collection technique used was questionnaire distribution. The data analysis tool used was multiple linear regression. The results of this study indicate that lifestyle, brand image, and e-wom have an effect on Unisba students' purchasing interest in Skintific skincare products. Students feel that buying skincare is a lifestyle and necessity, as well as brand image, and e-wom built from Skintific products make consumers continue to use the product. Skintific itself already has a good brand image, uses good quality ingredients, and has a good opinion in the eyes of consumers so that this good product quality can increase purchasing interest.